Structural and biochemical characterization of poliovirus RNA-dependent RNA polymerase fidelity and translocation - Sholders, Aaron J., author; Peersen, Olve, advisor; Bailey, Susan M., committee member; Laybourn, Paul, committee member; Luger, Karolin, committee member; Woody, Robert W., committee member (Colorado State University. Libraries, 2006)
Picornaviruses are small positive-sense single-stranded RNA viruses that result in a number of pathological conditions including foot-and-mouth disease, heart disease, poliomyelitis, and the common cold. Upon infection the small RNA genome is translated into a single polypeptide that is subsequently cleaved by c/s-acting proteases into ~12 viral proteins needed to carry out the viral life cycle. The last protein in the polypeptide is an RNA-dependent RNA polymerase whose primary function is genome replication. The N-terminus of the RNA-dependent RNA polymerase of poliovirus (3Dpol) is specifically buried within a tight pocket at the base of the fingers domain. Our lab has shown that the integrity of this pocket must be maintained for the proper positioning of Asp238, allowing it to form a hydrogen bond with the 2'-OH of the incoming NTP. If proper positioning of Asp238 is not maintained the polymerase will be unable to act as a catalyst for poliovirus genome replication. Recently the Kirkegaard and Andino laboratories isolated a poliovirus strain that was resistant to the effects of the antiviral nucleoside analog drug ribavirin (RTP). This strain contained a single point mutation within 3Dpol, changing glycine 64 to a serine (G64S). Glycine 64 comprises a portion of the N-terminus binding pocket and forms two hydrogen bonds to glycine 1. The structure of the 3Dpol G64S mutant demonstrates that the loss of conformational flexibility at residue 64 results in the expansion of the exterior portion of the N-terminal binding pocket. Structural alignments of the G64S structure with the native protein also reveal larger structural changes at a helix located in the index finger of the polymerase. In addition to movements within the index finger, the Gly64 mutant exhibited density suggestive of an alternate conformation for a loop consisting of residue 288-292. Biochemical and structural investigation of these residues indicates that the loop does indeed exist in two separate and stable conformations. Furthermore, the ability of the loop to switch between these two conformations is essential for proper functioning of the polymerase and mutations designed to inhibit loop flexibility lead to translocation defects. These data, in combination with the Gly64 data, are providing us with a better understanding of the molecular events in a complete catalytic cycle of the enzyme.
Keywords: biochemistry; virology